Enzymatic toxins from snake venom: structural characterization and mechanism of catalysis - Kang, Tse Siang; Georgieva, Dessislava; Genov, Nikolay; Murakami, Mario T.; Sinha, Mau; Kumar, Ramasamy P.; Kaur, Punit; Kumar, Sanjit; Dey, Sharmistha; Sharma, Sujata; Vrielink, Alice; Betzel, Christian; et al. (Wiley-Blackwell, 2011)
Snake venoms are cocktails of enzymes and non-enzymatic proteins used for both the immobilization and digestion of prey. The most common snake venom enzymes include acetylcholinesterases, l-amino acid oxidases, serine proteinases, metalloproteinases and phospholipases A2. Higher catalytic efficiency, thermal stability and resistance to proteolysis make these enzymes attractive models for biochemists, enzymologists and structural biologists. Here, we review the structures of these enzymes and describe their structure-based mechanisms of catalysis and inhibition. Some of the enzymes exist as protein complexes in the venom. Thus we also discuss the functional role of non-enzymatic subunits and the pharmacological effects of such protein complexes. The structures of inhibitorenzyme complexes provide ideal platforms for the design of potent inhibitors which are useful in the development of prototypes and lead compounds with potential therapeutic applications.
Keywords: Acetylcholinesterase; l-amino acid oxidase; metalloproteinase; phospholipase A2; Serine proteinase